2020
DOI: 10.2991/jegh.k.200102.002
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of ARV Therapy Among TB–HIV Patients in Indonesia Prolongs Survival Rates!

Abstract: Background: The HIV epidemic remains a public health problem with rising tuberculosis (TB) numbers around the world. Antiretroviral (ARV) therapy (ART) is essential to increase the survival of patients with TB-HIV coinfection. The aim of this study is to investigate the effect of ARV treatment initiation within TB treatment duration for the survival of patients with TB-HIV coinfection. Methods: This is a retrospective cohort study of patients with TB-HIV coinfection and who were ARV naive from Prof. Dr. Sulian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Similar to previous studies, [ 25 , 26 ] our multivariate model demonstrated that ART initiation was significantly associated with higher odds of mortality among HIV-positive TB patients. Based on the available evidence, the European AIDS clinical society recommends the following: “ART should be started as soon as possible (within 2 weeks of initiating TB treatment) regardless of CD4 count.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous studies, [ 25 , 26 ] our multivariate model demonstrated that ART initiation was significantly associated with higher odds of mortality among HIV-positive TB patients. Based on the available evidence, the European AIDS clinical society recommends the following: “ART should be started as soon as possible (within 2 weeks of initiating TB treatment) regardless of CD4 count.…”
Section: Discussionsupporting
confidence: 89%
“…[24] Tuberculosis can occur at any CD4 cell level; however, when CD4 levels are low, infection with other pathogens progresses As a result, when CD4 cell levels are low, in addition to active highly active ART and anti-TB therapy, the patient's immune system should be improved to enhance the treatment of other pathogens and reduce the occurrence of death. Similar to previous studies, [25,26] our multivariate model demonstrated that ART initiation was significantly associated with higher odds of mortality among HIV-positive TB patients. Based on the available evidence, the European AIDS clinical society recommends the following: "ART should be started as soon as possible (within 2 weeks of initiating TB treatment) regardless of CD4 count.…”
Section: Discussionsupporting
confidence: 89%
“…[ 29 30 31 ] It has also been shown that survival in HIV-TB co-infected can be improved by initiating ART at an appropriate time after starting of TB treatment. [ 27 32 ] Furthermore, treating physicians should use clinical judgement while starting ART to avoid mortality due Immune Reconstitution Syndrome. [ 33 ] Baseline CD4 counts at the time of diagnosis was another factor associated with mortality in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral therapy had more People Living with HIV (PLHIV) and thus it was anticipated that the incidence and mortality will decrease. Preexposure prophylaxis, viral suppression leading to the concept of ‘Undetectable = Untransmittable’ (U = U), and antenatal regimens were expected to further reduce the transmission of the virus [ 10 , 11 ]. HIV infections vary by regions, even within countries [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%